Photocatalytic degradation of Direct Brown RN dye in the presence of ZnO nanoparticles - Islam, ASM A; Ferdous, T; Das, AK; Karim, MM; Masum, SM (Bangladesh Journal of Scientific and Industrial Research, 2015)
The ZnO nanoparticle was prepared by using Zn(NO3)2.6H2O and NaOH under optimum reaction conditions and the prepared nanoparticle was characterized by UV-visible spectroscopy, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), energy dispersion X-ray spectroscopy (EDX) and scanning electron microscopy (SEM). The sunlight irradiated photocatalytic degradation of Direct Brown RN dye was studied using ZnO nanoparticle. The results of this investigation revealed that in the presence of sunlight, catalyst load of 0.5 g?L-1 and time of contact of 40 min, ZnO nanoparticle showed substantial capability of destroying Direct Brown RN dye from solution. An actual leather effluent containing Brown RN as a major constituent along with other dyes and dyeing auxiliaries was treated using ZnO and the reduction in the chemical oxygen demand (COD) of the treated effluent revealed almost complete destruction of the organic molecules along with color removal. Bangladesh J. Sci. Ind. Res. 50(1), 1-6, 2015